The Distribution Process of the Housing Stimulant Grants Program (BSPS) during COVID-19 Pandemic Situation in Muncan Village, Karangasem Regency - Juniartini, Ni Luh Putu; Juniartha, I Wayan; Setiawan, I Nyoman Anom Fajaraditya (Badan Riset dan Inovasi Daerah Provinsi Bali, 2020)
Purpose: The purpose of this study is to know the existence of BSPS as a government program through PUPR and the review focuses on Muncan Village, Karangasem Regency, as one of the beneficiary areas. The program follows the decisions, directions, rules, and procedures established by the provincial government of Bali. Research methods: The data are analyzed to separate criteria related to problems and solutions, and also solutions based on procedures and purposely determine informants based on specific criteria and considerations. Findings: Constraints were complicated by the emergence of the Covid-19 pandemic, which has an impact on various lines globally. Particular action needs to be taken primarily by TFL with the community. In addition to having to carry out procedures and rules in the distribution of aid, preventive measures addressing various field conditions also need to be considered. The analysis is divided into two categories: conditional on BSPS verification activities to keep going and initiatives to address the Covid-19 pandemic crisis in the field. Implications: The various obstacles faced are expected to become a consideration or study for the next period, especially with things that are unpredictable and are force majeure along with the team that is tasked directly in the field.